2022
DOI: 10.3390/nano12040597
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Vibrational Spectrometry of Stable Radicals—Necklaced Graphene Molecules

Abstract: The article presents results of an extended virtual experiment on graphene molecules performed using the virtual vibrational spectrometer HF Spectrodyn that exploits semiempirical Hartree-Fock approximation. The molecules are composed of flat graphene domains surrounded with heteroatom necklaces. Not existing individually, these molecules are met in practice as basic structure units of complex multilevel structure of all sp2 amorphous carbons. This circumstance deprives the solids’ in vitro spectroscopy of rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…A detailed description of the code is given elsewhere [17]. All of the calculations discussed in the current paper were performed using the AM1 version of the code in the UHF approximation since all of the studied DTs are open-shell molecules [13,18]. It should be noted that such an approach, similar in essence, but less categorically formulated, was practically realized by Yamada's team previously by applying to both rGO and graphene oxide (GO) [19].…”
Section: Digital Twins → Virtual Device → It Productmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the code is given elsewhere [17]. All of the calculations discussed in the current paper were performed using the AM1 version of the code in the UHF approximation since all of the studied DTs are open-shell molecules [13,18]. It should be noted that such an approach, similar in essence, but less categorically formulated, was practically realized by Yamada's team previously by applying to both rGO and graphene oxide (GO) [19].…”
Section: Digital Twins → Virtual Device → It Productmentioning
confidence: 99%
“…A comprehensive VVS analysis of IR absorption and the Raman scattering spectra of bare graphene domains has only recently been conducted. [13]. In light of the analytic focus of the current study, there is a need to briefly repeat its main issues.…”
Section: General Frequency Kits Of Bare Graphene Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many studies, the properties of these substances can be further identified using Raman spectroscopy [ 30 , 32 , 35 ], which is a simple, fast, and nondestructive detection technique [ 36 ]. The D band (located near 1350 cm −1 ) and G band (located near 1580 cm −1 ) can be used as the two main representative Raman peaks for GFNs [ 37 , 38 ].…”
Section: The Fate Of Gfns In Plantsmentioning
confidence: 99%